The spatial dimension of risk : how geography shapes the emergence of riskscapes - Müller-Mahn, Hans-Detlef. (Earthscan risk in society series ;, 2013)
"Through its exploration of the spatial dimensions of risk, this book offers a brand new approach to theorizing risk, and significant improvements in how to manage, tolerate and take risks. A broad range of risks are examined, including natural hazards, climate change, political violence, and state failure"--